The Final Stages of Slip and Volcanism on an Oceanic Detachment Fault at 13°48′N, Mid‐Atlantic Ridge. (14th September 2018) - Parnell‐Turner, R. E.; Mittelstaedt, E.; Kurz, M. D.; Jones, M. R.; Soule, S. A.; Klein, F.; Wanless, V. D.; Fornari, D. J.
Abstract: While processes associated with initiation and maintenance of oceanic detachment faults are becoming better constrained, much less is known about the tectonic and magmatic conditions that lead to fault abandonment. Here we present results from near‐bottom investigations using the submersible Alvin and autonomous underwater vehicle Sentry at a recently extinct detachment fault near 13°48′N, Mid‐Atlantic Ridge, that allow documentation of the final stages of fault activity and magmatism. Seafloor imagery, sampling, and near‐bottom magnetic data show that the detachment footwall is intersected by an ~850 m‐wide volcanic outcrop including pillow lavas. Saturation pressures in these vesicular basalts, based on dissolved H2 O and CO2, are less than their collection pressures, which could be explained by eruption at a shallower level than their present depth. Sub‐bottom profiles reveal that sediment thickness, a loose proxy for seafloor age, is ~2 m greater on top of the volcanic terrain than on the footwall adjacent to the hanging‐wall cutoff. This difference could be explained by current‐driven erosion in the axial valley or by continued slip after volcanic emplacement, on either a newly formed or pre‐existing fault. Since current speeds near the footwall are unlikely to be sufficient to cause significant erosion, we favor the hypothesis that detachment slip continued after the episode of magmatism, consistent with growing evidence that oceanic detachments can continue to slip despite hosting magmatic intrusions. Key Points: Autonomous underwater vehicle and submersible surveys carried out over inactive detachment fault on Mid‐Atlantic Ridge Sediment thickness and volatile content of lavas were used to track tectonic activity Seafloor observations suggest that slip continued after a volcanic intrusion into detachment fault footwall